Design, synthesis, X-ray studies, and biological evaluation of novel macrocyclic HIV-1 protease inhibitors involving the P1′-P2′ ligands. Issue 21 (1st November 2017) - Ghosh, Arun K.; Sean Fyvie, W.; Brindisi, Margherita; Steffey, Melinda; Agniswamy, Johnson; Wang, Yuan-Fang; Aoki, Manabu; Amano, Masayuki; Weber, Irene T.; Mitsuya, Hiroaki
Graphical abstract: Abstract: Design, synthesis, and evaluation of a new class of HIV-1 protease inhibitors containing diverse flexible macrocyclic P1′-P2′ tethers are reported. Inhibitor5a with a pyrrolidinone-derived macrocycle exhibited favorable enzyme inhibitory and antiviral activity ( K i  = 13.2 nM, IC50  = 22 nM). Further incorporation of heteroatoms in the macrocyclic skeleton provided macrocyclic inhibitors5m and5o . These compounds showed excellent HIV-1 protease inhibitory ( K i  = 62 pM and 14 pM, respectively) and antiviral activity (IC50  = 5.3 nM and 2.0 nM, respectively). Inhibitor5o also remained highly potent against a DRV-resistant HIV-1 variant.